Impairment in Emotional Intelligence May Be Mood-Dependent in Bipolar I and Bipolar II Disorders - Kuo, Shih-Yu; Chang, Yun-Hsuan; Wang, Tzu-Yun; Tseng, Huai-Hsuan; Huang, Chih-Chun; Chen, Po See; Lane, Hsien-Yuan; Yang, Yen Kuang; Lu, Ru-Band (Frontiers in Psychiatry, 2021)
Background: An emotional intelligence (EI) deficit has been noticed in euthymic bipolar spectrum disorder (BD) patients. However, whether this deficit is affected by mood or subtype is unclear. Objectives: The aim of this study was to investigate whether an EI deficit is mood-dependent, and which mood symptoms have more impact on EI in BD. Methods: Two hundred and thirty participants aged between 18 and 65 years old were recruited (130 BD patients (51 bipolar I disorder (BDI) and 79 bipolar II disorder (BDII)): 39.2% males; 91 healthy controls (HCs): 48.4% males). The Mayer–Salovey–Caruso Emotional Intelligence Test (MSCEIT), which contains experiential and strategic EI ratings, was used to assess social cognition. The Hamilton Depression Rating Scale (HDRS) and the Young’s Mania Rating Scale (YMRS) were used for evaluating the severity (HAMD and YMRS scores ≦7 were euthymic (BDeut) and HAMD YMRS sores ≧8 were episodic (BDepi)). Analyses of covariance (ANCOVA) were performed, with adjustment for background information between the BD patients and HCs. Results: The results showed that, compared to the HCs, the BDeut patients showed no difference in any MSCEIT measures, while the BDepi patients showed lower scores in all MSCEIT measures, except for perceiving emotions. In addition, a main effect of mood state instead of BD subtype was found for the managing emotions branch (p < 0.0007). Stepwise regression showed that the duration of illness and HDRS scores were correlated with the scores in the strategic area of the MSCEIT, while age and YMRS scores were more relevant to the scores in the experiential area of the MSCEIT. Conclusion: The results confirm that an EI deficit is mood-dependent in BD patients. In addition, a depressive mood is more related to the strategic EI area, whole a manic mood is correlated with the experiential EI area. Understanding the different domains of EI deficits in BD patients may be helpful for developing interventions for BD.